Increased extracellular heat shock protein 90α in severe sepsis and SIRS associated with multiple organ failure and related to acute inflammatory-metabolic stress response in children. Issue 35 (August 2016) - Fitrolaki, Michaela-Diana; Dimitriou, Helen; Venihaki, Maria; Katrinaki, Marianna; Ilia, Stavroula; Briassoulis, George
Abstract : Abstract: Mammalian heat-shock-protein (HSP) 90α rapidly responses to environmental insults. We examined the hypothesis that not only serum HSP72 but also HSP90α is increased in the systemic inflammatory response syndrome (SIRS), severe-sepsis (SS), and/or sepsis (S) compared to healthy children (H); we assessed HSP90α relation to (a) multiple organ system failure (MOSF) and (b) inflammatory-metabolic response and severity of illness. A total of 65 children with S, SS, or SIRS and 25 H were included. ELISA was used to evaluate extracellular HSP90α and HSP72, chemiluminescence interleukins (ILs), flow-cytometry neutrophil-CD64 (nCD64)-expression. HSP90α, along with HSP72, were dramatically increased among MOSF patients. Patients in septic groups and SIRS had elevated HSP90α compared to H ( P  < 0.01). HSP90α was independently related to predicted death rate and severity of illness; positively to HSP72, nCD64, ILs, length of stay, days on ventilator, and fever; negatively to HDL and LDL ( P  < 0.05). The HSP72 was increased in SS/S and related negatively to HDL and LDL ( P  < 0.05). Serum HSP90α is markedly elevated in children with severe sepsis and is associated with MOSF. Better than the HSP72, also increased in SS, SIRS, and MOSF, HSP90α is related to the inflammatory stress, fever, outcome endpoints, and predicted mortality and inversely related to the low-LDL/low-HDL stress metabolic pattern.